Quality Culture: Starting Point To Form Competitive Human Resources - Andika Prasetya Nugraha; Sarmini Sarmini; Sabri Sabri; Mulyadi Mulyadi; Andi Hidayatul Fadlilah (Yayasan Pendidikan Penelitian Pengabdian Algero, 2024)
The